2010
DOI: 10.1038/emboj.2010.219
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae Mre11/Rad50/Xrs2 and Ku proteins regulate association of Exo1 and Dna2 with DNA breaks

Abstract: Single-stranded DNA constitutes an important early intermediate for homologous recombination and damage-induced cell cycle checkpoint activation. In Saccharomyces cerevisiae, efficient double-strand break (DSB) end resection requires several enzymes; Mre11/Rad50/Xrs2 (MRX) and Sae2 are implicated in the onset of 5 0 -strand resection, whereas Sgs1/Top3/Rmi1 with Dna2 and Exo1 are involved in extensive resection. However, the molecular events leading to a switch from the MRX/Sae2-dependent initiation to the Exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
266
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(301 citation statements)
references
References 53 publications
31
266
3
1
Order By: Relevance
“…Mre11, one of the first proteins bound to DSB sites, provides a structural platform for the initial recruitment of Dna2 to DSB sites (49,50). It was noted that the level of Dna2 associated near the DSB sites increased during resection (50). This observation cannot be explained only by the proteinprotein interactions between Dna2 and Mre11 (or Sgs1 at the later stage).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Mre11, one of the first proteins bound to DSB sites, provides a structural platform for the initial recruitment of Dna2 to DSB sites (49,50). It was noted that the level of Dna2 associated near the DSB sites increased during resection (50). This observation cannot be explained only by the proteinprotein interactions between Dna2 and Mre11 (or Sgs1 at the later stage).…”
Section: Discussionmentioning
confidence: 67%
“…Dna2 cleaves selectively the 5Ј-overhang ssDNA of the Y-structured DNA, producing a 3Ј-ss overhang (8). Mre11, one of the first proteins bound to DSB sites, provides a structural platform for the initial recruitment of Dna2 to DSB sites (49,50). It was noted that the level of Dna2 associated near the DSB sites increased during resection (50).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, the need of MRX for end resection can be bypassed in the absence of Ku (26,27). Interestingly, we found that elevated MMEJ due to Ku70 deficiency was greatly reduced by loss of Mre11 or Mre11 nuclease activity ( Fig.…”
Section: Mre11mentioning
confidence: 67%
“…We showed that the nuclease activity of human Mre11 is required for initial end resection and cannot be substituted by other nucleases such as BLM and Exo1. Third, loss of Ku70 in yeast can bypass the requirement of MRN for end resection (26,27), whereas, in mammalian cells, elevated MMEJ and HR in Ku70-or Ku80-deficient cells are still dependent on the Mre11 complex and Mre11 nuclease activity, even with DSB ends generated by the I-SceI endonuclease in our study. This finding is supported by the in vitro analysis using Xenopus extracts where depletion of Mre11 blocks end resection from restriction enzyme-generated DSBs from the very initial step at the first nucleotide (45).…”
Section: Mmej Is Used To Repair Dsbs Occurring At Collapsed Replicationmentioning
confidence: 74%
See 1 more Smart Citation